Shaken Baby Syndrome - Donna Davis; Suzanna Smith (EDIS)
FAR0410, a 2-page transcript of the Family Album Radio Program broadcast by Donna Davis and Suzanna Smith, describes this preventable form of child abuse, and provides suggestions from the Child Abuse Prevention Project. Includes references. Published by the UF Department of Family Youth and Community Sciences, March 2009.